Using Cassava And Sweet Potato To Produce Biethanol As An Alternative Energy Sources - Yasinta Sindy Pramesti,Hesti Istiqlaliyah,Yayan Srinatriyo (International Conference on Industrial Revolution for Polytechnic Education, 2021)
The current fuel demand in Indonesia has increased. In contrary, fossil oil supply has decreased. It will be concerned if fossil oil run out. So, it is urged to replace it with bioethanol. Compared to fossil fuels, bioethanol has the advantages of being renewable, providing cleaner burning and producing no green-house gases. Biotehanol is a fuel derived from renewable sources of feedstock. There are a lot of natural resources that need to be investigated for ethanol production such as sweet potato and cassava. This study was used experimental method. Ethanol yielded from cassava was higher than sweet potato. Highest effective fermentation time was at 72 hours at any condition. Adding inokulum Zymomonas mobilis was increased the ethanol yielded on cassava and sweet potato. Inoculum concentration at 14% was the most effective and highest ethanol yielded. This treatment was produced ethanol yielded about 59% for cassava and 47% for sweet potato.